If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -11 = 15 Reorder the terms: -11 + z = 15 Solving -11 + z = 15 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + z = 15 + 11 Combine like terms: -11 + 11 = 0 0 + z = 15 + 11 z = 15 + 11 Combine like terms: 15 + 11 = 26 z = 26 Simplifying z = 26
| 10-a=36 | | 12x+5=12x-31 | | 4x^2+43x+30=0 | | 170-7x=20x+17 | | x^2+16x+81=x^2+18x+81 | | 2(-8-6x)=-52 | | 3x/2-2=7 | | 812x*183x^2+52=813 | | 3(-8-6x)=-52 | | 64x^2-116x+22=0 | | 3x^2+4x+15=0 | | 0=x^2-4x+16 | | -4(6x-2)=-208 | | 6(-2x-8)=-96 | | -4z(-5z-10)-4(-2z-9)= | | 25.8+z=30.6 | | 2(-7x+8)=72 | | 2(-7c+8)=72 | | .16x+.50x+x=120 | | y=1/2(1)-2 | | (v+4)(v+6)=0 | | y=1/2(0)-2 | | -6x-6=-6+2x | | 4x+27=6x | | y=1/2(-2)-2 | | y=1/2(-4)-2 | | 10+5x=4x+64 | | 12x-7=10x+13 | | -8-4n=19 | | 2y-6=5y+9 | | 9p^3+73p+70=0 | | y=-1/4(-2)-6 |